The effect of growth, intellectual capital, financial performance on firm value - Indah Ayu Johanda Putri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Modern companies increasingly recognize the importance of non-financial factors in influencing company performance and value. One important non-financial factor is intellectual capital, which includes human resources, customer relationships, and innovation capabilities. Company growth is a crucial component in establishing a company's value. Very few studies have looked at the relationship between growth, intellectual capital, and financial performance and business value at the same time. This study investigates how business value in the banking sector is impacted by growth, intellectual capital, and financial performance. This study takes a quantitative approach, gathering secondary data from the financial and annual reports of companies in the banking industry listed on the IDX between 2018 and 2022. Purposive sampling was employed to pick the 63 companies that comprise the research sample. The Partial Least Square (PLS) method was used to evaluate the data. The findings demonstrated that corporate growth, intellectual capital, and financial performance positively and significantly impacted firm value. To increase company value, businesses should consider non-financial elements like corporate development, intellectual capital, and financial success.